Methodology of Moral Education in Lithuanian General Schools - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2007)
An article deals with the problem of moral education in Lithuania, especially in General Schools. The analysis of different Curricula of moral education in last fifteen years is done and explicated, stressing change of methodology, which is basic and essential for curricula understanding and prognoses of the perspectives in moral education. Lithuanian Curricula’s for General Schools’ methodology is compared with methodologies those are recently suggested in other European countries. The broader Lithuanian social changes context is analysing also: social development features, changing of students thinking and moral values, teachers training, dominant textbooks, Lithuanian educational low toward moral education. The main point of this article as the result of investigation of curricula is eclectic methodology of recent curricula, which is not negative feature in this situation. Eclectic style of methodology is consequence of educational innovations, efforts of educationalists, trying to gather advantages of all types of minding and teaching with a task to fill up educational gaps; those appeared in soviet time and have their continuity till now. The direction of this eclectic methodology is oriented on dialog, which is very important for social life, social communication and values. This invention is treated as a modern construct of Lithuanian moral education curricula, which correspond with European contemporary trends in moral education. The problem of disadvantages in moral field and education in Lithuania is evaluated as a result of other obstacles for effective embodying of Curricula in Lithuanian educational life and is rising as a question for farther investigations.